Magnetic, Photophysical and Thermal Properties of Complexes of Iron(II) with Structurally Different Schiff Bases - Abdullah, Norbani; Azil, Afiq; Marlina, Anita; Linahafizza M. Noor, Nur (Asian Journal of Chemistry, 2015)
Three Fe(II) complexes of structurally different Schiff bases i.e., [Fe(L1)2](BF4) (1), [Fe2(OOC(CH2)14CH3)2(L2)(H2O)2] (2) and [Fe2(OOC(CH2)14CH3)2(L3)(H2O)4]·2.5H2O (3), were synthesized and characterised for potential uses as spin crossover and low band gap materials with metallomesogenic properties. Complex 1 was obtained in a one-pot reaction involving Fe(BF4)2 with L1, while compounds 2 and 3 were obtained by step-wise reactions involving [Fe(OOC(CH2)14CH3)2(EtOH)] with H2L2 and H2L3, respectively. At room temperature, compound 1 has a low-spin Fe(II) atom while both compounds 2 and 3 have two high-spin Fe(II) atoms. The values for the optical band gap (Eg) were 1.8 eV for compound 1, 1.9 eV for compound 2 and 2.3 eV for compound 3. These complexes were thermally stable, with decomposition temperature of 260 °C for compound 1, 205 °C for compound 2 and 250 °C for compound 3. Complexes 1 and 2 exhibited mesomorphisms while 3 was not mesomorphic.